Search for neural correlates of object and panorama learning in mushroom body extrinsic neurons of bumblebees - Inga Fuchs; Benjamin Paffhausen; Randolf Menzel (Journal of Comparative Physiology A, 2026)
A laboratory-based setup was developed that allowed us to train bumblebees to a rewarding object (local cue) in the context of a panorama and simultaneously to record extracellularly the neural activity of units interpreted as mushroom body extrinsic neurons (MBENs). This setting simulates conditions flower visiting bees face when foraging excluding the compass related conditions. The bumblebees navigated between the colony and the test/feeding arena on their own motivation, starting from a fully functional colony with a queen. They learned by sucrose reward a specific feeding place marked by the rewarding object local cue (blue pyramid cylinder) placed in a fixed spatial relation to the panorama (matching panorama). Spontaneous choice tests and extinction tests revealed enhanced search behavior for the learned matching condition. Single or multiple (up to three) simultaneously recorded neurons referred to here as units revealed learning-related differences either by increased, decreased or unchanged neural activity. We focused on tests in which the local cue was presented in the same area as the panorama (learned condition: matched) or in separate areas (mismatched condition). Neural activity differed in these two test conditions. This learning effect did not depend on the areas tested, indicating that the whole arena had been learned as an environment in which the local cue and the panorama were spatially related. No changes in neural activity were found for head direction toward the goal (local cue, panorama, matched or mismatched), distance to the goals or the gateway. No place-cell-like activity patterns were found. Significant neural effects were also seen in some units during multiple walks between local cue and panorama in mismatch tests.

Balancing biodiversity and economics: Using robust Pareto-optimisation to quantify ecological–economic trade-offs in German mixed beech forests - Julia Klenke; Volker von Groß; Jasper M. Fuchs; Larissa R. Topanotti; Benjamin Wildermuth; Carmen Alicia Rivera Pérez; Jing-Zhong Lu; Likulunga Emmanuel Likulunga; Thomas Knoke; Carola Paul (Ambio, 2026)
Biodiversity loss threatens forest ecosystem stability and functioning, while measures to enhance biodiversity trade-off with economic performance. Native tree-species mixtures are promoted to support associated taxa but usually underperform economically compared to non-native species, both in pure and admixed stands. Quantifying ecological–economic trade-offs remains challenging due to uncertainties in economic and biodiversity indicators. Using empirical data on economic (land rent/annuity) and biodiversity indicators (species richness) of five forest taxa from Central German forests, we applied multicriteria optimisation to forest stand-type compositions. We assess the compositional shift of pure (beech, spruce, Douglas-fir) and mixed stand types (beech–spruce, beech–Douglas-fir) under increasing biodiversity targets, accounting for uncertain indicator provision. Stand-type portfolios became more diversified with increasing biodiversity targets. Biodiversity-economic trade-offs were efficiently reduced by incorporating Douglas-fir (in pure and mixed stands) into the portfolio. However, enhancing biodiversity created economic loss, underscoring the need for financial compensation schemes.

Bumblebees (Bombus terrestris) forage on plants treated with glyphosate-based herbicides despite potential behavioral consequences - Kimmo Kaakinen; Satu Ramula; Benjamin Fuchs; James D. Blande; Eva-Maria Vaajamo; Marjo Helander (Environmental Research, 2025)

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

Plant metabolic responses to soil herbicide residues differ under herbivory in two woodland strawberry genotypes - Benjamin Fuchs; Marjo Helander; Kari Saikkonen; Petre I. Dobrev; Radomira Vankova; James D. Blande; Juha-Pekka Salminen; Niko Luntamo; Anne Muola (Science of The Total Environment, 2024)

Archaeopedological reconstruction of Middle Bronze Age subsistence farming in SW-Germany from sedimentary archives in the Western Allgäu - Sascha Scherer; Benjamin Höpfer; Katleen Deckers; Markus Fuchs; Ellen Kandeler; Eva Lehndorff; Johanna Lomax; Sven Marhan; Christian Poll; Wroth Kristen; Thomas Knopf; Thomas Scholten; et al. (Geoderma Regional, 2023)

Synthetic oxygen carrier C28 compared to natural ores for chemical looping combustion with solid fuels in 80 kWth pilot plant experiments - Fleiß Benjamin; Priscak Juraj; Fuchs Josef; Müller Stefan; Hofbauer Hermann (Fuel, 2023)

Ecosystem consequences of herbicides: the role of microbiome - Suvi Ruuskanen; Benjamin Fuchs; Riitta Nissinen; Pere Puigbò; Miia Rainio; Kari Saikkonen; Marjo Helander (Trends in Ecology & Evolution, 2023)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Responses to larval herbivory in the phenylpropanoid pathway of Ulmus minor are boosted by prior insect egg deposition - Johanna Schott; Benjamin Fuchs; Christoph Böttcher; Monika Hilker (Planta, 2022)
Main conclusion Elms, which have received insect eggs as a ‘warning’ of larval herbivory, enhance their anti-herbivore defences by accumulating salicylic acid and amplifying phenylpropanoid-related transcriptional and metabolic responses to hatching larvae. Abstract Plant responses to insect eggs can result in intensified defences against hatching larvae. In annual plants, this egg-mediated effect is known to be associated with changes in leaf phenylpropanoid levels. However, little is known about how trees—long-living, perennial plants—improve their egg-mediated, anti-herbivore defences. The role of phytohormones and the phenylpropanoid pathway in egg-primed anti-herbivore defences of a tree species has until now been left unexplored. Using targeted and untargeted metabolome analyses we studied how the phenylpropanoid pathway of Ulmus minor responds to egg-laying by the elm leaf beetle and subsequent larval feeding. We found that when compared to untreated leaves, kaempferol and quercetin concentrations increased in feeding-damaged leaves with prior egg deposition, but not in feeding-damaged leaves without eggs. PCR analyses revealed that prior insect egg deposition intensified feeding-induced expression of phenylalanine ammonia lyase ( PAL ), encoding the gateway enzyme of the phenylpropanoid pathway . Salicylic acid (SA) concentrations were higher in egg-treated, feeding-damaged leaves than in egg-free, feeding-damaged leaves, but SA levels did not increase in response to egg deposition alone—in contrast to observations made of Arabidopsis thaliana . Our results indicate that prior egg deposition induces a SA-mediated response in elms to feeding damage. Furthermore, egg deposition boosts phenylpropanoid biosynthesis in subsequently feeding-damaged leaves by enhanced PAL expression, which results in the accumulation of phenylpropanoid derivatives. As such, the elm tree shows similar, yet distinct, responses to insect eggs and larval feeding as the annual model plant A. thaliana.

Contrasting Effects of Grass - Endophyte Chemotypes on a Tri-Trophic Cascade - Benjamin Fuchs; Eric Kuhnert; Jochen Krauss (Journal of Chemical Ecology, 2020)
Systemic grass-endophytes of the genus Epichloë symbiotically infect the above-ground plant parts of many grass species, where they produce alkaloids in a grass- and endophyte-specific manner that are toxic or deterrent to herbivores. An increasing number of studies show cascading negative effects of endophyte-derived alkaloids that extend to higher trophic levels, harming beneficial insects, including those that control aphid populations. Lacewings are one of the major biological aphid controls, and are especially resistant to insecticides and pollutants, but their susceptibility to endophyte infection in the food chain has never been studied. Our study found variability in aphid population growth depending on the endophyte-grass chemotype, where aphid population growth was lowest on chemotypes known for producing high amounts of loline alkaloids. We also showed that larval and pupal development and mortality of the Common Green Lacewing ( Chrysoperla carnea ) was, in a non-choice experiment, not affected by endophyte infection in the food chain. This is a first indication that lacewings might be resistant to endophyte-derived alkaloids and could be robust biocontrol agents when applied together with endophyte-infected grass, possibly replacing chemical pesticides.

Enhanced aphid abundance in spring desynchronizes predator–prey and plant–microorganism interactions - Benjamin Fuchs; Tatjana Breuer; Simone Findling; Markus Krischke; Martin J. Mueller; Andrea Holzschuh; Jochen Krauss (Oecologia, 2017)

Peramine and Lolitrem B from Endophyte-Grass Associations Cascade Up the Food Chain - Benjamin Fuchs; Markus Krischke; Martin J. Mueller; Jochen Krauss (Journal of Chemical Ecology, 2013)

Dominance of the odometer over serial landmark learning in honeybee navigation - Randolf Menzel; Jacqueline Fuchs; Leonard Nadler; Benjamin Weiss; Nicole Kumbischinski; Daniel Adebiyi; Sergej Hartfil; Uwe Greggers (The Science of Nature, 2010)

Epidemiology of an aphid nontransmissible potyvirus in fields of nontransgenic and coat protein transgenic squash - Marc Fuchs; Amit Gal-On; Benjamin Raccah; Dennis Gonsalves (Transgenic Research, 1999)